The language phenomenon of ecolalia in autism spectrum disorders and the right and challenges of inclusive education - De Castro Fregnan, Marina (2018)
The present work aims to analyze the linguistic phenomenon of the echolalia in Autism Spectrum Disorder (ASD), addressing the rights and challenges, as well as the mechanisms of inclusion in the educational space. This is an asystematic review of literature that leads to the reflection and problematization of the inclusion policies of people with ASD. Children with ASD usually present difficulties in the functional use of language, independent of the conceptual approach, representing one of the fundamental aspects of the pathology. It is necessary to implement specific education and training of teachers and professionals in the field of education, and the tendency of students with ASD to semantic difficulties and in more serious cases, in the pragmatics of language.